As notícias e seus critérios na perspectiva da rede - Cezar, Gustavo Buss (2014)
A common hypothesis when thinking about journalism in the current context of information flow, established in the network, is that it is properly adjusted and modified to this dynamic. In the internet flow, information seem detached from journalism, and due to the parallel narrative, journalism is no longer the only voice heard. With the scaling of time and space, we wonder how journalism would be different in this environment, specifically, the newsworthiness criteria as sealer of this transformation. Thus, we have established for this thesis, the newsworthiness criteria as an object of study and have as a reference and basis for understanding journalism and news from the perspective of network. Newsworthiness criteria were identified and theorized in a social, cultural and technological quite different from their current, so it makes the relevance of this study, review them in the context of the network. We make it studying with a methodological base of analyzing the news of 10 selected news agencies in order to identify the newsworthiness criteria present in their content. Our research results, unlike what we expected at the beginning of our study make us think of journalism as a living, oxygenated and aware of your surroundings organism, establishing constant changes at the same time, we observed that preserves its identity and newsworthiness.